1998
DOI: 10.1115/1.2834432
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of Super Alloys at Elevated Temperatures

Abstract: This paper provides the results of an extensive sliding wear testing program to evaluate wear resistance of several material couples currently used for high temperature applications such as ground based gas turbines and aircraft engines. Nickel and cobalt base superalloys and iron base stainless steels were tested in different combinations, and their wear rates compared to determine optimal wear resistance. The results show that an alloy’s wear resistance is highly dependent on operating temperature and its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Lawen Jr et al 51 investigated and compared high temperature (290 ∘ C, 345 ∘ C, 425 ∘ C, and 815 ∘ C) wear behavior of cobalt, nickel-based superalloys along with iron-based stainless steel. These alloys were tested in different combinations and optimal wear resistance was calculated among the couple.…”
Section: Classification Of Superalloysmentioning
confidence: 99%
“…Lawen Jr et al 51 investigated and compared high temperature (290 ∘ C, 345 ∘ C, 425 ∘ C, and 815 ∘ C) wear behavior of cobalt, nickel-based superalloys along with iron-based stainless steel. These alloys were tested in different combinations and optimal wear resistance was calculated among the couple.…”
Section: Classification Of Superalloysmentioning
confidence: 99%
“…During the friction process of nickel-based superalloy at high temperature, it has been found that a thin and physically homogeneous oxide layer was formed on the component surface [17][18][19][20]. The formed oxide layer was also known as the glaze-layer, which was reported to contribute to the low coe cient of friction (COF) and wear rate for NBSC superalloys at high temperature [21,22]. A widely recognized speculation was that the glaze-layer was formed by compacting and sintering the wear particles produced during sliding process with the presence of heat [18, 23,24].…”
Section: Introductionmentioning
confidence: 99%